2008
DOI: 10.1590/s0101-20612008000400017
|View full text |Cite
|
Sign up to set email alerts
|

Conservação de maçã minimamente processada com o uso de películas comestíveis

Abstract: Uma tendência crescente na atualidade são os vegetais Minimamente Processados (MP), ou seja, frutas e hortaliças que tenham sido submetidas a qualquer alteração física que mantenha seu estado fresco. Este processamento inclui as operações de seleção, lavagem, sanitização, descascamento, corte, centrifugação, embalagem, armazenamento e comercialização (MORETTI, 1999).As alterações por deterioração fisiológica nos MP ocorrem especialmente devido às injúrias nos tecidos, geralmente reduzindo o período de conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
20

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 7 publications
4
19
0
20
Order By: Relevance
“…the metabolic activities of the fruit reducing the degradation of polysaccharides and changes in the soluble solids content. Similar results were found by Fontes et al (2008), who studied the application of coatings of alginate on fresh-cut apples stored at 2 °C for 13 days. The author describes that the content of soluble solids in the control sample and samples treated with alginate showed significant differences (p ≤ 0.05) during storage.…”
Section: Characterization Of Pearssupporting
confidence: 86%
See 1 more Smart Citation
“…the metabolic activities of the fruit reducing the degradation of polysaccharides and changes in the soluble solids content. Similar results were found by Fontes et al (2008), who studied the application of coatings of alginate on fresh-cut apples stored at 2 °C for 13 days. The author describes that the content of soluble solids in the control sample and samples treated with alginate showed significant differences (p ≤ 0.05) during storage.…”
Section: Characterization Of Pearssupporting
confidence: 86%
“…Therefore, the pH of the fruit increases with a decrease in acidity, and thus it is used as an indicator of this variation. Fontes et al (2008) used an edible coating of alginate on minimally processed apples stored at 2 °C for 13 days and found that the pH of the fruits remained unchanged during storage. Bico et al (2009) Same capital letters in the same line and same lowercase letters in the same columns indicate that the samples did not differ significantly (p ≥ 0.05).…”
Section: Characterization Of Pearsmentioning
confidence: 99%
“…A study by Fontes, Sarmento, Spoto and Dias (2008) demonstrated that the use of starch, dextrin and sodium alginate were effective to maintain the values of Chroma a* lower than the control sample during 13 days of storage. These results agree with the present work, since the use of croaker protein isolate along with MMT as coatings were efficient to keep the pieces of apples with a more pleasing color for longer when compared with the control sample.…”
Section: Colormentioning
confidence: 99%
“…• Alginato de sódio (AS) a 0,5%: aquecimento da suspensão de 0,5 g de alginato de sódio/100 mL de água potável em banho a 70 °C, sob agitação constante (FONTES et al, 2008). …”
Section: Preparo Das Soluções Filmogênicasunclassified
“…Tais diferenças entre os tratamentos com e sem película se acentuaram após o 9º dia de armazenamento. Fontes et al (2008) 11,5 ± 0,3 aA 11,0 ± 0 aB 11,0 ± 0 aB 11,2 ± 0,2 aAB 3º 11,7 ± 0,5 aA 10,6 ± 0,4 aB 10,6 ± 0,5 abB 10,5 ± 0,3 bB 6º 11,5 ± 0,4 aA 10,1 ± 0,3 bB 10,5 ± 0,2 bB 10,3 ± 0,1 bcB 9º 10,8 ± 0,1 bA 9,7 ± 0,1 cdB 9,5 ± 0,4 cB 9,6 ± 0,4 dB 12º 10,7 ± 0,3 bA 9,3 ± 0,2 dC 8,9 ± 0,5 dD 9,8 ± 0,1 cdB 15º 10,4 ± 0,1 bA 10,0 ± 0,3 bcA 9,6 ± 0,2 cB 9,5 ± 0,4 dB pH 1º 4,8 ± 0,1 ca 4,7 ± 0,1 ca 4,8 ± 0,1 cda 4,7 ± 0 dea 3º 5,1 ± 0 aba 5,1 ± 0 aa 5,1 ± 0 aa 5,1 ± 0 aa 6º 5,0 ± 0 ba 4,9 ± 0,1 ba 4,9 ± 0 bca 5,0 ± 0,1 ba 9º 5,0 ± 0,1 ba 4,7 ± 0,1 cb 5,1 ± 0 aa 4,8 ± 0 cdb 12º 5,2 ± 0 aa 4,9 ± 0,3 bb 4,9 ± 0,1 bb 4,8 ± 0 cb 15º 5,0 ± 0,1 aba 4,5 ± 0,1 dc 4,7 ± 0 db 4,6 ± 0,2 eb Acidez titulável (g ácido cítrico 100 g …”
Section: Análises Microbiológicasunclassified